Hypofractionated radiotherapy in post mastectomy locally advanced breast cancer: a study from a regional cancer center in North East India - Bhattacharyya, Mouchumee; Kalita, Apurba Kumar; Medhi, Partha Pratim; Jagtap, Vikas; Sunku, Rubu; Hassan, Fahim Arman; Kalita, Manoj; Krishnatreya, Manigreeva; Kataki, Amal Chandra (International Journal of Research in Medical Sciences, 2018)
Background: Adjuvant radiotherapy has increased local-regional and overall survival rates in breast cancer. Conventional fractionation delivering 50-60 Gray (Gy) over 5-6weeks is a standard approach. A shorter duration of hypofractionated treatment will be more convenient for patients and treatment providers if found safe and equally effective. Methods: Around 50 high risk breast cancer patients who underwent mastectomy were enrolled and randomized into the study arms- CF (Conventional Fractionation) Arm (50Gy/25 Fr @ 2 Gy/fraction/day 5 days a week over 5weeks) and HF (Hypo-Fractionation) arm (40.05 Gy/15 Fr @ 2.67 Gy/fraction/day 5 days a week over 3weeks). Treatment related acute and late toxicities, loco-regional recurrence; distant metastasis and survival rates were recorded for comparison. Results: Twenty-five patients were enrolled in each arm with baseline characters well matched. At median follow up of 44 months, OS was 80% in HF arm against 64% in CF arm (p-value: 0.292). HF arm also showed better DFS at 4 years of 76% compared to 64% in CF arm (p-value: 0.411). Although the difference was not significant statistically, the Hazard Ratio of 1.543 (95% CI: 0.549-4.339) for DFS and 1.801 (95% CI: 0.603-5.377) for OS indicated trends towards better outcomes in HF arm in terms of disease control and survival. Acute and late toxicities were also lesser in HF arm, though not statistically significant (all p-values >0.05). Conclusions: In post mastectomy setting, HFRT is comparable to CFRT in terms of safety and efficacy, will be more convenient for patients and care givers and hence can be a routine standard practice.